2020
DOI: 10.30699/ijp.2020.106598.2222
|View full text |Cite
|
Sign up to set email alerts
|

Napsin-A Expression, a Reliable Immunohistochemical Marker for Diagnosis of Ovarian and Endometrial Clear Cell Carcinomas

Abstract: KEYWORDS ABSTRACTClear cell carcinoma, Diagnosis, Endometrium, Ovary, Napsin-A Scan to discover online Background & Objective: Clear cell carcinomas (CCC) differ from other types of ovarian and endometrial carcinomas in biology, behavior and response to chemotherapy. Histopathologic diagnosis may be challenging in some situations which necessitates immunohistochemistary (IHC) assessment. In this study we investigated the diagnostic utility of Napsin-A in diagnosis of ovarian and endometrial CCCs.Methods: Ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Napsin A is a well-established marker for clear cell carcinomas in female genital tract cancers of both the ovary and endometrium (10,28,34). In the current study, we found a total of 5% of cases (3/60) expressing Napsin A.…”
Section: Discussionsupporting
confidence: 48%
“…Napsin A is a well-established marker for clear cell carcinomas in female genital tract cancers of both the ovary and endometrium (10,28,34). In the current study, we found a total of 5% of cases (3/60) expressing Napsin A.…”
Section: Discussionsupporting
confidence: 48%
“…It is a marker with high sensitivity and high specificity for CCC. Sensitivity, specificity, PPV, and NPV are 88%, 98%, 98%, and 91% have been reported (28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 89%
“…Triple-negative breast cancers, however, may not express GCDFP-15, GATA 3, or mammaglobin, and in such cases, SOX-10 may be helpful ( 16 ). On the other hand, PAX8 expression is a sensitive marker for endometrial carcinoma ( 17 ) and napsin A supports the clear cell subtype ( 18 ). Nonetheless, it must be recognized that some overlap exists between the immunohistochemical markers seen in breast and endometrial cancers.…”
Section: Discussionmentioning
confidence: 99%